Analysis Of Electrical Power Requirements For Arduino Based Wireless Starter Control Module In Motorcycles (Universitas Pendidikan Indonesia, 2025)
This study aims to design a wireless starter system module based on Arduino, equipped with a motorcycle anti-theft security system, and to analyze the electrical power consumption of the module during operation. The development of this motorcycle control module is motivated by the damage to engine components caused by the infrequent warming up of the engine before use and the high rate of motorcycle theft. This study uses a descriptive method to outline the results of the module development and the analysis of electrical power requirements. Data collection begins with the preparation phase, followed by module development, testing, and analysis. Data is presented in the form of tables and graphs. The results of this study show that (1) An Arduino-based wireless starter control module, which can be operated with an Android smartphone, has been developed; (2) the highest power consumption is 3.24 watts when the key switch and starter switch are activated; (3) continuous use of this module will quickly deplete the motorcycle battery. when the security mode is active, the battery lasts approximately 27 hours, and when the security mode is off, the battery lasts approximately 42 hours.